The "Inscrutably Chinese" Church: How Narratives and Nationalism Continue to Divide Christianity - Faries, Nathan (Lexington Books, 2010)
The first half of the twenty-first century promises to be a time of great change for the Christian church in the PeopleOs Republic of China. The situation is complex and fluid, and the information gap between those on the inside and those outside of China is still significant, though shrinking. The OInscrutably ChineseO Church moves readers nearer to the Chinese Christian experience, as Nathan Faries helps foreign readers to see with greater clarity just how Chinese Christians view their government and themselves in relation to those ruling powers. There still exists a measure of inscrutability about China and its complex relationship with religion that must be explained to the outsider. It is this gap in understanding_between insider points of view within China and those outsiders seeking knowledge about the Christian faith in China_that Faries seeks to close.